Human Monkeypox Virus (hMPXV) Remerges - Another Global Health Concern during the COVID-19 Disaster - Nagarajan, Prithiviraj; Sivanandham, Mohan; Rangarajalu, Kumar; Howlader, Anusheela; Port Louis, Leena Rajathy (Journal of Liaquat University of Medical & Health Sciences, 2023)
The increase in human monkeypox virus (hMPXV) cases amidst the COVID-19 pandemic has raised fear among the general public. The monkeypox virus and the now-extinct smallpox virus belong to the orthopox family of viruses. Although first discovered in 1958, Monkeypox was only well recognized outside the sub-Saharan African countries until the world experienced a monkeypox pandemic in May 2022. The virus is common in some areas of Africa and is often spread through close contact with an infected person or animal. However, recent international trade, travel, and tourism developments have caused viral outbreaks outside Africa. The most recent pandemic in 2022 has been strange because epidemiologists have not found a link between cases and the virus’s ability to spread through sexual contact. The structural and pathogenic activities of the virus that attack host cells need to be better understood. Because of this, it is important to know how viruses and the immune system work together to develop effective ways to treat and prevent diseases. To summarize existing research on Monkeypox, we conducted a narrative review using the MEDLINE, EMBASE, PUBMED, and Scopus databases to look at simultaneous zoonotic pandemics caused by the SARS-CoV-2 or COVID-19 coronavirus and presented the most to date information on the symptoms, epidemiology, diagnosis, prevention, and treatment of Monkeypox. However, more research on epidemiological details, ecology, and virus biology in endemic areas is required to understand the virus better and prevent further human infection.